Incidence and Risk Factors for Hypoxia in Deep Sedation of Propofol for Artificial Abortion Patients - Fang, Yiling; Xu, Yaru; Cao, Silu; Sun, Xiaoru; Zhang, Hui; Jing, Qi; Tian, Li; Li, Cheng (Frontiers in Medicine, 2022)
Background: Respiratory depression is a life-threatening adverse effect during deep sedation . This study took induced abortion as an example to investigated the factors related to hypoxia caused by propofol during intravenous anaesthesia . Methods:308 patients who underwent painless artificial abortion in the outpatient department of Shanghai Tenth People’s Hospital between 1 November 2019 and 30 June 2020 were divided into two groups according to whether the patients had hypoxia (SpO2＜95%).During the operation, anaesthesia process and surgical operation-related information of the two groups were analysed. The univariate analysis results were further incorporated into logistic regression analysis for multivariate analysis to determine the independent risk factors affecting hypoxia. Results：Univariate analysis revealed that BMI (21.80 ± 2.94 vs. 21.01 ± 2.39；P=0.038,95% confidence interval (CI)=[-1.54,-0.04]), propofol dose (15.83 ± 3.21 vs. 14.39 ± 3.01；P=0.002,CI=[-2.34,-0.53]), and menopausal days (49.64 ± 6.03 vs. 52.14 ± 5.73；P=0.004,CI=[0.79,4.21]), State Anxiety Inventory score (51.19 ± 7.55 vs. 44.49 ± 8.96；P＜0.001,CI=[-9.26,-4.15]), and Self-rating Anxiety Scale score (45.86 ± 9.48 vs. 42.45 ± 9.88；P=0.021,CI=[-6.30,-0.53]) were statistically significant risk factors for hypoxia during the operation. Logistic regression analysis showed that propofol dosage, menopausal days, and State Anxiety Inventory score were independent risk factors for hypoxia. Conclusion：Patient anxiety affects the incidence of hypoxia when undergoing deep intravenous anaesthesia with propofol. We can further speculate that alleviating patient anxiety can reduce the incidence of hypoxia. Trial registration: This trial is registered with http://www.chictr.org.cn(Number: ChiCTR2000032167).